Differential Expression Analysis Identifies Novel Regulatory Genes in Endometriosis - Ian Pranandi (CV. Publikasi Indonesia, 2026)
Background: Endometriosis is a chronic estrogen-dependent inflammatory disorder associated with pelvic pain and infertility. Despite its high prevalence, the molecular regulatory mechanisms underlying disease progression remain incompletely understood. Objective: This study aimed to identify differentially expressed genes (DEGs) and prioritize key regulatory candidates involved in endometriosis pathogenesis using integrative bioinformatics analysis. Methods: Publicly available human transcriptomic datasets comparing endometriotic lesions and normal endometrial tissues were analyzed. Data were normalized and subjected to differential expression analysis using adjusted p-value < 0.05 and |log2 fold change| ≥ 1 as thresholds. Functional enrichment analysis and protein–protein interaction (PPI) network construction were performed to identify enriched pathways and hub genes. Results: A total of 326 significant DEGs were identified, including 189 upregulated and 137 downregulated genes. Enrichment analysis revealed predominant involvement of inflammatory signaling, angiogenesis, extracellular matrix remodeling, and steroid hormone response pathways. Network analysis identified IL6, STAT3, VEGFA, and MMP9 as central upregulated hub genes, while PGR and HOXA10 were among the key downregulated regulators associated with progesterone resistance. Conclusion: Endometriosis exhibits coordinated activation of inflammatory–angiogenic networks and suppression of steroid signaling pathways. The identified hub genes represent potential biomarkers and therapeutic targets, warranting further experimental validation.